Indisponibilidade de bens na improbidade administrativa: compatibilidade constitucional, convencional e regime jurídico - Gahyva, Saulo Rondon (2024)
This investigation aims to develop a critical analysis of the provisional remedy of asset unavailability in cases of administrative misconduct, a topic extensively revised during the reform of Law No. 8,429/1992. The objective is to argue that the new regime of the provisional remedy of asset unavailability is perfectly aligned with constitutional and conventional provisions. Following a legislative and constitutional history of administrative misconduct in Brazil, the legal nature of the substantive norms of administrative misconduct is analyzed, followed by an investigation into the procedural legal regime of administrative misconduct actions highlighting the evolution of debates on jurists’opinions and on precedents about this matter. This study argues about the possibility or impossibility of including administrative misconduct actions in the collective microsystem, opposing major jurists’ understandings as well as the precedents established before Law No. 14,230/2021. Concluding the first part, the procedural legal regime of administrative misconduct actions is identified under Law No. 8,429/1992 of the Code of Civil Procedure (CPC/2015), and by the constitutional procedural guarantees of punitive processes, thus defining the procedure's structure. Once the administrative misconduct action is defined as a sui generis civil action, the investigation moves on to analyze the procedural legal regime of asset unavailability, followed by the constitutional and conventional compatibility of the new regime. Additionally, the appropriateness of this new regime is investigated in light of the nature of the administrative misconduct action, through the procedural aspects of the new law. The investigation then stresses the new regime's intertemporal right and the new provisions' impact on the established positions in the Superior Court of Justice (STJ) regarding asset unavailability. Finally, it is concluded that the innovations in the provisional remedy of asset unavailability comply with the normative system of administrative misconduct actions. Then, the assumptions outlined in this work can be used to solve other relevant issues related to provisional remedies in administrative misconduct actions.